Laser-powder bed fusion of pre-mixed Inconel718-Cu powders: An experimental study. (November 2021) - El Hassanin, A.; Silvestri, A.T.; Napolitano, F.; Scherillo, F.; Caraviello, A.; Borrelli, D.; Astarita, A.
Abstract: Pre-mixing powders with different characteristics to generate feedstocks for Laser-Powder Bed Fusion (L-PBF) of custom materials is becoming increasingly attractive to the Additive Manufacturing community, both in academia and industry. The aim of this work is to demonstrate the validity of the L-PBF process applied to pre-mixed Inconel 718 and Copper (Cu) gas-atomized powders. L-PBF experiments were conducted with powders blends of the selected materials, pre-mixed with a fluidized bed at different Cu percentage addition and investigating the influence of the laser energy input and layer thickness. The results, analyzed in terms of density, hardness, microstructure and tensile properties, proved the effectiveness of L-PBF for the custom powder feedstocks. The pre-mixed materials experienced an intimate melting during the process and the parts relative density was always >98%. An expected decrease of the mechanical properties was observed, of about the 24% of Vickers hardness and about the 40% for the tensile strength considering the worst case, due to the Cu addition and molten pool evolution during L-PBF. Highlights: Gas-atomized Inconel 718 and Cu pre-mixed blends were processed with L-PBF. 5% and 20% wt. of Cu were considered for this study. The effects of layer thickness and energy input were also investigated. The relative density of the L-PBF parts was always >98%. Hardness and tensile strength decreased, as expected, due to Cu addition.